The Use of Arak Bali as a Fuel Influence on Fire Characteristics of Combustion - Sukadana, I Gusti Ketut; I Gusti Komang Dwijana; I Putu Widiarta (Natural Sciences Engineering and Technology Journal, 2024)
Analyze the characteristics of gas fuel from arak Bali, like shape and flame speed. Test characteristics such as methanol and ethanol content material gas from arak Bali, after it tested the gas fuel combustion characteristics of arak Bali such as the shape and speed of flame. Testing characteristics such as the content of methane and ethanol gas from arak Bali performed in the forensic laboratory while testing the ignition characteristics of the shape and speed of fuel from evaporating arak Bali done using a helle-shaw cell combustion chamber model. Air mixture ratio variations with gas fuel from arak Bali is 24/1, 25/1, 26/1, 27/1, 28/1, 29/1, 30/1 and 31/1. The observed effect is the shape and speed of the premixed flame propagation in the helle-shaw cell combustion chamber model. The results of the study, the moisture content of the basic ingredients of gas fuel arak Bali consisting of 40% methanol and 60% ethanol. Gas fuel from arak Bali has a stoichiometry air-fuel ratio of 30/1. Getting closer to the stoichiometry air-fuel ratio, flame color changes from reddish color faded to red, reddish blue, blue and bright blue last. The maximum speed of propagation of fire occurring in stoichiometry air-fuel ratio is 328.33 cm/sec.